Sistem Pengecaman Bentuk Berdasarkan FPGA - Zainal Ariffin, Nur Bayani (Universiti Sains Malaysia, 2005)
Pattern recognition is an important part to human being daily life, because we always recognize the patterns in all aspects our works. Pattern recognition means that the definition, identification and the classification by deciding the characteristics of that pattern which is need to be known. It is always can be an application to whatever course and now have been used widely among the people. Hence, a pattern recognition system by an array of chemical sensor application will be developing based on FPGA. It is purposely to develop hardware for that application. Beside that, an algorithm also will be used to implement this system. Fuzzy Inferences System has been chosen as the method for designing the system. This method will be implementing to the system since it is a popular way to represent pattern recognition system. There are 3 main processes that have to be done by this method, they are fuzzification, rules inferences engine and defuzzification. The Xilinx Foundation 2.1 Series based on FPGA is the methodology for development this system.